Thoughts on Teacher Training Needs in Colombia in Times of Liquid Societies - Lopez Rodriguez, Rubiela Rocio (2020)
Upon reflecting on teacher training needs from various perspectives, it is important to consider teacher training strategies required to confront the disastrous socio-economic and cultural consequences produced by liquid modernity. International organizations emphasize the importance of teacher education. Yet, the composition of curriculums for Education majors at universities in Colombia has many gaps and does not include collaborative work or institutional objectives within their teacher training priorities, for example. Many fallacies have also been detected when formulating new educational policies in Colombia, which are misconstrued as necessary to uphold educational quality, but which, actually, violate the professionalization of teachers. Given that today´s society, characterized by neoliberal policies, savage capitalism and the destruction of life, faces specific educational needs. new strategies must be proposed to prepare teachers to face the nefarious economic and cultural consequences of liquid modernity.